Corporate finance and its implications in the development of micro and smalls enterprises - Huánuco Perú 2011 - Martel-Zevallos, David J. (2019)
Whereas the responsibility of society as a whole to establish fair balance points for micro an small entrepreneurs, who go to the instances of financial institutions for funding. The formulated objectives and hypotheses have been achieved and tested using inferential statistics, following strictly the scientific method. Informality rates are very high and companies do not seem to be interested in formalized by the high costs that the process entails. Access to financial credit is the main problem, for the modest investment in a micro business, and in many cases do not get appropriate qualification to enable them to participate in the credit market; on the contrary to present guarantor or without them, interest rates are higher than recorded inflation annually. The above suggests that the main problems of MYPES are the result of stabilization policy and accelerated trade liberalization. The degree of development attained by Micro and Small enterprises in Huánuco, is acceptable and do not obey the use of lines of corporate financing. The lack of uniform promotion, that is, discrimination observed by company and sector sizes, highlight the existence of inadequate economic policies and lacking of a comprehensive approach to support MYPES. The study concludes that corporate finance, contributes to an efficient financial management of the activities and expectations of Micro and Small Enterprises in Huánuco.